Human adipose tissue-derived stromal/stem cells promote migration and early metastasis of triple negative breast cancer xenografts. - Brian G Rowan; Jeffrey M Gimble; Mei Sheng; Muralidharan Anbalagan; Ryan K Jones; Trivia P Frazier; Majdouline Asher; Eduardo A Lacayo; Paul L Friedlander; Robert Kutner; Ernest S Chiu (PLoS ONE)
Background Fat grafting is used to restore breast defects after surgical resection of breast tumors. Supplementing fat grafts with adipose tissue-derived stromal/stem cells (ASCs) is proposed to improve the regenerative/restorative ability of the graft and retention. However, long term safety for ASC grafting in proximity of residual breast cancer cells is unknown. The objective of this study was to determine the impact of human ASCs derived from abdominal lipoaspirates of three donors, on a human breast cancer model that exhibits early metastasis. Methodology/principal findings Human MDA-MB-231 breast cancer cells represents "triple negative" breast cancer that exhibits early micrometastasis to multiple mouse organs [1]. Human ASCs were derived from abdominal adipose tissue from three healthy female donors. Indirect co-culture of MDA-MB-231 cells with ASCs, as well as direct co-culture demonstrated that ASCs had no effect on MDA-MB-231 growth. Indirect co-culture, and ASC conditioned medium (CM) stimulated migration of MDA-MB-231 cells. ASC/RFP cells from two donors co-injected with MDA-MB-231/GFP cells exhibited a donor effect for stimulation of primary tumor xenografts. Both ASC donors stimulated metastasis. ASC/RFP cells were viable, and integrated with MDA-MB-231/GFP cells in the tumor. Tumors from the co-injection group of one ASC donor exhibited elevated vimentin, matrix metalloproteinase-9 (MMP-9), IL-8, VEGF and microvessel density. The co-injection group exhibited visible metastases to the lung/liver and enlarged spleen not evident in mice injected with MDA-MB-231/GFP alone. Quantitation of the total area of GFP fluorescence and human chromosome 17 DNA in mouse organs, H&E stained paraffin sections and fluorescent microscopy confirmed multi-focal metastases to lung/liver/spleen in the co-injection group without evidence of ASC/RFP cells. Conclusions Human ASCs derived from abdominal lipoaspirates of two donors stimulated metastasis of MDA-MB-231 breast tumor xenografts to multiple mouse organs. MDA-MB-231 tumors co-injected with ASCs from one donor exhibited partial EMT, expression of MMP-9, and increased angiogenesis.